2002
DOI: 10.1021/la010683b
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Thin Solid Films of Dioctadecyldimethylammonium Cinnamate Lamella Units That Control the Photostationary State of EZ Photoisomerizations

Abstract: UV illumination of dioctadecyldimethylammonium cinnamates (C18 trans-cin and C18 cis-cin) was found to result in the E-Z photoisomerization of the cinnamate moieties in self-assembling multilamella films. In the present case, a common photostationary state (pss), which can usually be observed in solution, was not seen in the photolysis of the self-assembled material films of C18 trans-cin and C18 cis-cin having a bimolecular (bilayer)-unit lamellar structure. Both the E-and Z-isomers are difficult to isomerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The preparation method of the polymer films can also play a significant role in the photochemical behavior upon UV exposure. As an example, Ohtani et al have shown that the photoreactivity of cinnamate groups in dioctadecyldimethylammonium/cinnamate ions self-assembled films varies according to the heat treatment of the films before photoirradiation which leads to different molecular organizations. Also, in a previous work, we have reported that cinnamate groups of modified cellulosic polymers mainly undergo either dimerization in spin-coated films or isomerization in networks synthesized with an exogeneous cross-linker …”
Section: Introductionmentioning
confidence: 99%
“…The preparation method of the polymer films can also play a significant role in the photochemical behavior upon UV exposure. As an example, Ohtani et al have shown that the photoreactivity of cinnamate groups in dioctadecyldimethylammonium/cinnamate ions self-assembled films varies according to the heat treatment of the films before photoirradiation which leads to different molecular organizations. Also, in a previous work, we have reported that cinnamate groups of modified cellulosic polymers mainly undergo either dimerization in spin-coated films or isomerization in networks synthesized with an exogeneous cross-linker …”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that structural changes in 1:1 ion-pair composite bilayer films consisting of dioctadecyldimethylammonium bromide and cinnamic acid take place not only in dispersion but also when cast on glass slides, and that such changes can be induced by a photochemical E − Z photoisomerization and/or a [2+2] photocycloaddition of the cinnamate regions. These self-assembling structures have been revealed to be variable with the photochemical transformations of the component olefins.…”
Section: Introductionmentioning
confidence: 99%